A educação inclusiva no ensino superior: disciplina LIBRAS e a preparação para o ensino do português como L2 - Leitão, Nayara Araujo Duarte (2021)
Teacher training for the inclusive context is still a little explored theme in some teacher training courses. In the case of deafness and Libras, their knowledge in graduation is limited to one subject in the curriculum, which limits a lot of relevant discussions on teacher education involving inclusive education, Libras and the teaching of Portuguese in Higher Education. This way, to develop our research, we list the following four research questions (1) What is the perspective of teaching the undergraduate professor in the Sign Language discipline for undergraduate courses?; (2) What teaching strategies are used by the undergraduate teacher to contribute to teacher training?; (3) What is the view of undergraduate students on Sign Language in the undergraduate course?; and (4) Is it clear to students the concept of Portuguese as an L2 for the deaf? In order to answer these questions, this research aimed to analyze the perceptions of the teacher and students in the teaching of Libras in the process of teacher training, with regard to the education of the deaf. As specific objectives, we outline the following: (1) Identify and describe the main documents that legislate undergraduate courses with regard to the deaf person; (2) Analyze the perceptions of the teacher of the Libras discipline and of the students about their training / experience, the structure of the university and the Libras discipline and its possible impacts on the training of students; and (3) Understand how Libras' teaching principles for Language courses are implemented in the classroom. We theoretically conducted our discussion based on studies of the current legislation on the inclusion of deaf students, in teacher education studies (TARDIF, 2007; GARCEZ e SCHLATTER, 2017) and teaching Portuguese as an L2 (LODI, 2011; PEREIRA, 2014; FURLANETO, 2019). The methodology adopted was of a qualitative nature, with the case study based on the analysis of the effectiveness of a Libras discipline in the undergraduate course in Letters, in a Higher Education Institution, in the city of Cajazeiras, Paraíba - Brazil. For that, we analyzed (1) the main official documents that govern the discipline in the Higher Education Institution in question, (2) the interviews made with the teacher and 17 students who attended the Libras discipline in the degree course in Letters and, finally, (3) the field diary notes made during the observed classes. After analyzing the data, we concluded that the current legislation guides the teaching and training of teachers with regard to the context of deafness, however, the implementation of these laws still needs to advance further. We also found that the teacher perceives the Libras discipline in undergraduate courses as a way to raise awareness and build knowledge with students not only in relation to the structures of languages, but also from the point of view of raising awareness regarding the rights and duties of students deaf and, for this, the teacher uses several strategies such as the study of legislation, theoretical texts, but also the practice of the use of signs, as a way to acquire vocabulary. Finally, we found that, for students, the discipline had great relevance for training, despite being limited, especially with regard to time - only one academic semester. In addition, they demonstrate to understand the Portuguese language as L2 for students with deafness.